ANALISIS KIMIA 6 JENIS KAYU JAWA BARAT - Jacob Ando (Jurnal Penelitian Hasil Hutan, 1988)
The result  of  chemical analyses of 6 wood species from  West Java is presented  in this report.  The analyses comprised of determination of  cellulose,   lignin,  pentosan   and  extractive  contents.The result shows  that  specific  gravity  ranges from  0.40  to 0.47,  cellulose  content   from  45.4  to  60.6 percent, lignin from  22.5 to 33,2  percent,  pentosan  from  15,1 to 18, 7 percent  and extractive from  0.8 to 2.7 percent.